2021
DOI: 10.3390/nano11071742
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Long-Term Exposure to Low Concentrations of MWCNTs Induces an Epithelial-Mesenchymal Transition in BEAS-2B Cells

Abstract: In the field of nanotechnology, the use of multi-walled carbon nanotubes (MWCNTs) is growing. Pulmonary exposure during their production, use, and handling is raising concerns about their potential adverse health effects. The purpose of this study is to assess how the physical characteristics of MWCNTs, such as diameter and/or length, can play a role in cellular toxicity. Our experimental design is based on the treatment of human bronchial epithelial cells (BEAS-2B) for six weeks with low concentrations (0.125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It has already been demonstrated that long-term in vitro exposures to non-cytotoxic doses of NMs are able to induce the acquisition of different hallmarks of cancer in exposed cells, such as morphological cell changes, secretion of matrix metalloproteinases, anchorageindependent cell-growth capacity, and migration ability, as observed after exposures to cobalt nanoparticles [4], zinc oxide nanoparticles [5], silver nanoparticles [6], and multiwalled carbon nanotubes (MWCNT) [7]. On the other hand, emerging evidence indicates that NM exposure can cause different epigenetic changes correlated with gene-expression alterations [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that long-term in vitro exposures to non-cytotoxic doses of NMs are able to induce the acquisition of different hallmarks of cancer in exposed cells, such as morphological cell changes, secretion of matrix metalloproteinases, anchorageindependent cell-growth capacity, and migration ability, as observed after exposures to cobalt nanoparticles [4], zinc oxide nanoparticles [5], silver nanoparticles [6], and multiwalled carbon nanotubes (MWCNT) [7]. On the other hand, emerging evidence indicates that NM exposure can cause different epigenetic changes correlated with gene-expression alterations [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Kim SH et al [ 11 ] discovered the skin sensitization potential of silica nanoparticles, Kim IY [ 8 ] the ROS production and the apoptosis induced by TiO 2 in their model, and Valentino the impairment of gene expression in young and elderly rat lungs after nanoTiO 2 inhalation [ 12 ]. Meanwhile, the team of Barthel and Seidel showed that long-term exposure to low concentrations of multiwalled carbon nanotubes could lead to an epithelial mesenchymal transition in BEAS-2B cells [ 13 ].…”
mentioning
confidence: 99%
“…Nanomaterials 2023,13, 1968. https://doi.org/10.3390/nano13131968 https://www.mdpi.com/journal/nanomaterials…”
mentioning
confidence: 99%